FAKTOR PENGHAMBAT PENYEMBUHAN LUKA DI RS MELATI PERBAUNGAN - Mesrida Simarmata; Nurhaida Nurhaida (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Diabetes mellitus, a chronic metabolic disorder characterized by high blood sugar levels as a result of insulin insufficiency. This is due to a disruption in the definition of insulin production, the beta cells of the pancreas gland are due to the lack of responsiveness of the body's cells to insulin. Chronic wounds that are difficult to heal due to disruption of wound healing by systemic, local and other factors so that the wound does not heal with normal wound healing time. Chronic wounds occur because primary healing is delayed and repeated over a period of time. This research is a descriptive study, the aim of which is to look at